Strategi Komunikasi Pemanfaatan Key Opinion Leader dalam Meningkatkan Brand Awareness di Media Sosial - Dharmawan, Michelle Ruth; Yoedtadi, Moehammad Gafar (Prologia, 2024)
Brand Miss Daisy as a newcomer in the self-care and health industry in Indonesia consistently uses marketing communication strategies through opinion leaders on social media Instagram and TikTok. The purpose of this research is to find out and analyze whether the marketing communication strategy using Key Opinion Leader since the beginning of 2022 until now has succeeded in attracting consumer buying interest. Also to find out what challenges Miss Daisy faced from the beginning of planning to implementation. This research was conducted using a descriptive qualitative approach. The theories used are marketing communication theory, social media marketing theory, key opinion leader theory and brand awareness theory. The data collection technique was obtained through in-depth interviews with resource persons, both internal Miss Daisy and external resource persons. The data obtained from the research was analyzed using data analysis techniques and source triangulation. The research shows that marketing strategies using Key Opinion Leaders are closely related to content; it is this KOL content that will play a role in increasing consumer awareness of the brand and attracting their buying interest. Brand Miss Daisy sebagai pendatang baru dalam industri perawatan diri dan kesehatan di Indonesia secara konsisten menggunakan strategi komunikasi pemasaran melalui pemimpin opini di media sosial Instagram dan TikTok. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisa apakah strategi komunikasi pemasaran menggunakan Key Opinion Leader sejak awal tahun 2022 hingga sekarang berhasil menarik minat beli konsumen. Juga untuk mengetahui tantangan apa yang dihadapi Miss Daisy sedari awal perencanaan hingga implementasi. Penelitian ini dilakukan menggunakan pendekatan kualitatif deskriptif. Teori yang digunakan adalah teori komunikasi pemasaran, teori pemasaran media sosial, teori key opinion leader dan teori brand awareness. Untuk teknik pengumpulan data diperoleh melalui wawancara mendalam dengan para narasumber, baik internal Miss Daisy sampai narasumber eksternal. Data yang diperoleh dari penelitian dianalisis menggunakan teknik analisis data dan triangulasi sumber. Penelitian menunjukkan bahwa strategi pemasaran menggunakan Key Opinion Leader erat kaitannya dengan konten; konten KOL inilah yang akan berperan dalam meningkatkan kesadaran konsumen tentang merek dan menarik minat beli mereka.